Unusual products in the reactions of phosphorus(III) compounds with N=N, C equivalent to C or conjugated double-bonded systems - Swamy, K. C. Kumara; Balaraman, Ekambaram; Pavan, M. Phani; Kumar, N. N. Bhuvan; Kumar, K. Praveen; Kumar, N. Satish (Journal of Chemical Sciences, 2006)
The diversity of products in the reaction of diethyl azodicarboxylate (DEAD)/diisopropyl azodicarboxylate (DIAD) and activated acetylenes with PIII compounds bearing oxygen or nitrogen substituents is discussed. New findings that are useful in understanding the nature of intermediates involved in the Mitsunobu reaction are highlighted. X-ray structures of two new compounds (2-t-Bu-4-MeC6H3O)P (μ-N-t-Bu)2P+[(NH-t-Bu)N[(CO2]-i-Pr)(HNCO2-i-Pr)]](Cl-)(2-t-Bu-4-MeC6H3OH)(23)and [CH2(6-t-Bu-4-Me-C6H2O)2P(O)C(CO2Me)C-(CO2Me)CClNC(O)Cl] (33) are also reported. The structure of23 is close to one of the intermediates proposed in the Mitsunobu reaction.